(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
World practice shows that the share of the digital economy in gross digital product is considered one of the indicators of macroeconomic development of this state. The development of the digital economy is an important, strategic task for Uzbekistan, which determines its competitiveness on a global scale, and provides for the need for our state to create the necessary conditions for the development of this sphere, to stimulate this process